SISTEM MONITORING VOLUME TANGKI SOLAR MENGGUNAKAN SENSOR ULTRASONIC - Muhamad Ainur Rony; Falconi Falconi (Universitas Budi Luhur, 2013)
PT. Berca Hardayaperkasa has been one of the leading providers of Enterprise Information Technology (IT) and Test & Measurement (T&M) solutions in Indonesia, which is located in Building Berca. Jl. Abdul Muis No. 62, Central Jakarta. PT Berca Hardayaperkasa has its own building as its headquarters. To maintain stability of the company's performance stable electricity needed, therefore as a backup power, PT. Berca Hardayaperkasa pick the generator to maintain the stability of the tank where this generator diesel as fuel storage and current measurement of the tank volume is still done manually, which needed someone to come into a diesel tank to measure the volume of the tank using an iron rod is dipped in the tank and recorded disebuah form, then the results are stored in a recording of accounting regularly reported. Of these problems, the authors tried to make an experiment and manufacture of hardware and its software in the form of interface. Design method that is used as a process model or paradigm of software engineering in this paper is by using the method of the waterfall model of the system will assist officers in the generator tank volume monitoring in real time while also facilitate in making the report is based on the volume of diesel fuel tank level, besides the advantage of this system is the alarm that can inform the officer if a decline in volume at a certain level, not only that the system is also based on client - server which will allow officers to monitor the tank from any computer as long as the computer is connected to the network. After the experiment the authors conclude with the personnel system makes it easy to create reports and the officer can determine if a decline in the volume of the alarm through sent via email and voice alarm will sound when the volume of the tank is in levelcritical. Hopefully, this system can be used and further developed to monitor the volume of the tank at the pump. Keywords : Ultrasonic, Tank Solar Measurement